Antimicrobial Interaction between Endophytic Actinobacteria Associated with Listea Cubeba and Listea Cubeba Essential Oils Against Food Borne Bacteria - Vu, Thu Trang; Nguyen, Hai Van; Vu, Thi Hanhuyen; Phi, Quyet Tien; Do, Thi Yen; Chu, Ky Son (Old Journal, 2020)
The purpose of the study was to investigate the antimicrobial activity of endophytic actinomycetes isolated from Listea cubeba (L. cubeba) and its essential oil on two food-borne pathogenic bacteria Gram-positive Escherichia coli ATCC 25922 (E. coli) and Gram-positive Staphylococcus aureus ATCC 25923 (S. aureus) individual and in combination. The results indicated that 3 among 7 endophytic actinomycetes (MPT44, MPT42, MPT 62) showed antibacterial activity against tested strains with the antibacterial diameter ranging from 17 – 44 mm. Using the broth micro-dilution assay, minimum inhibitory concentration (MIC) of endophytic actinomycetes bacteria were from 6.25 to 25 µl/ml. From the indices of fractional inhibitory concentration (FIC) of the combination of L. cubeba essential oil and its endophytic actinomycetes, the synergistic effects were found against E. coli, S. aureus. The combination of L. cubeba essential oil and its endophytic actinomycetes broth culture enhances the antimicrobial efficacy gainst foodborne pathogens 3 to 8 times comparing with individual treatment. In addition, the combination use of essential oils and secondary metabolites from endophytic bacteria should be useful way to enhance food security.